REVITALITASASI KAIDAH KOPERASI DALAM SISTEM EKONOMI KERAKYATAN - A. Tulus Sartono (Faculty of Law, Universitas Diponegoro, 2010)
Cooperative as an economic movement of people has the function and the central role in building the economic capacity of members in particular and society in general. Realizing the role of the community with a better quality of life, progressive, independent, to strengthen the people's economic by making fair and prosperous society based on Pancasila and the Constitution of 1945. Cooperatives as legal entities are part of the economic system mst be independent, so as to uphold the principles of cooperation, and democracy in a cooperative.Kata Kunci : Cooperative, populist economics